Physiological Parameters Monitored on Bottlenose Dolphin Neonates (Tursiops truncatus, Montagu 1821) over the First 30 Days of Life - Barbara Biancani; Guillermo J. Sánchez-Contreras; Stefano Furlati; Francesco Benaglia; Carmen M. Arija; Claudia Gili (Animals, 2021)
Bottlenose dolphins (Tursiops truncatus) have been bred under human care for more than 60 years. Calves up to 30 days of life have presented the highest mortality rate, although comparable data for free-ranging neonates within this age group is not available. Husbandry measures to increase survivability have therefore been constantly improved. This work shows the results of a structured veterinary program that established the procedures to collect relevant physiological parameters on 13 calves during their first 30 days of life. Standardized observation protocols facilitated statistical analysis of the respiratory pattern, nursing, morphometric measurements and bloodwork. These allow early detection of health issues. Healthy neonates had longer apnea duration, despite the shape and size of the facility. The nursing pattern showed that successful calves started nursing 3 to 18 h postpartum. Although with different individual patterns, a steady increase in suckling time occurs during the first 24 h of life. The healthy neonates grew 0.428 ± 0.102 kg per day and the complete blood count profile, glucose, iron, blood urea nitrogen (BUN), total protein, Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Gamma-glutamyl transferase (GGT), creatinine and electrolytes values considered normal for healthy calves are provided. Furthermore, cholesterol, triglycerides, α-amylase, lipase, magnesium and cortisol are reported for the first time for such young calves. A list of indications for prompt intervention is included.